The Concept Of The Word Ṡamrah (Fruit) In The Quran (A Semantic Study By Toshihiko Izutsu) - Parbo, M. Guruh Hazian (STIQ Amuntai, 2024)
This article examines the conceptual meaning of the word ṡamrah (fruit) in the Quran using Toshihiko Izutsu's semantic approach. This study found that ṡamrah has a basic meaning as an edible plant product, but it also has a relational meaning that depends on the context in which it is used in the Quran. The word not only refers to physical fruits but also includes the results of human effort and blessings given by Allah. This article is a qualitative article and uses the analytical descriptive method in analyzing the verses containing the word ṡamrah. In addition, it highlights the importance of the word ṡamrah when looking at the semantic field and the concept of the word ṡamrah as a blessing in life through various verses that explain it. Patience in facing the test of lack of sustenance is also explained. This research also emphasizes ecological awareness by utilizing natural resources wisely which includes the word ṡamrah in it and maintaining environmental balance. Thus, this research provides an in-depth look at how the concept of the meaning of the word ṡamrah in the Quran can be applied in everyday life.